Analysis of the Effect of Corporate Governance on Financial Performance with Corporate Social Responsibility as an Intervening Variable (Study on Commercial Banks Listed on the Indonesia Stock Exchange for the Period 2018-2022) - Ramania, Shendy; Widyarti, Endang Tri (Master of Management, Faculty of Economics and Business, Diponegoro University, 2025)
Banks have a very strategic, important and crucial role in sustaining national economic development. Banks are profit-maximizing economic agents and operate to increase shareholder and stakeholder value. This means that shareholders are interested in value maximization, which can be achieved through the company's financial performance. This study discusses the effect of board size, audit committee, managerial ownership, and institutional ownership on the financial performance of Commercial Banks listed on the IDX for the 2018-2022 period through CSR. This study uses quantitative data types with secondary resources obtained through the financial statements of each bank downloaded through Bloomberg, the official website of the Indonesia Stock Exchange (www.idx.co.id) and annual reports downloaded from the website of each commercial bank for the period 2018-2022. The number of samples used was 12 commercial banks listed on the IDX for the period 2018-2022. The analysis method used in this research is a structural equation model (SEM) using an analytical tool in the form of SEM-PLS. The results of this study indicate that BOD has a significant positive effect on ROA, BOD has a significant positive effect on CSR, AC has a significant positive effect on ROA, AC has no effect on CSR, MO has no effect on ROA, MO has no effect on CSR, IO has no effect on ROA, MO has no effect on CSR, and CSR has no effect on ROA of commercial banks listed on the IDX in the 2018-2022 period.